Ecopreneurship-based urban farming assistance program for communities in the urban fringe area - Durrotun Nafisah; Ika Purnamasari; Isnawati Isnawati; Zulfin Rachma Mufidah (Universitas Muhammadiyah Malang, 2025)
Some of Deket Districts have changed the function of agricultural land into industrial, residential and service land. This area is an urban fairy area. Thus, the problem that arises is the narrowing of agricultural land which has an impact on the reduced amount of rice and fish production. This can create vulnerabilities to the household economy. community service that aims to increase agricultural production, income and sustainable food security through an ecopreneurship-based urban farming education and assistance approach This community service partner is the Karya Jaya 4 Farmers Group. The stages of community service are 1) Socialization and Preparation, partners provide yard land or small areas for urban farming trials; 2) Urban Farming Training, partners take part in technical training on making hydroponic aquaponic systems; 3) Technology Application, partners build installations by mutual cooperation (technical assistance from the service team) and maintain agricultural installations and record crop yields; 4) Monitoring and Evaluation, partners provide periodic reports on the progress of activities and engage in evaluation forums and reflection on program results; 5) Program Sustainability, partners are willing to be agents of change (champions) for program replication in other RT/RW and regular discussions related to sustainability and program development. The results of the service activities show an increase in the knowledge and skills capacity of members of the Karya Jaya 4 Farmers Group in the implementation of ecopreneurship-based urban farming. The partners successfully built and managed five units of a simple aquaponics-hydroponic system in the yard with a success rate of 85%. Overall, this activity contributes to increasing household food production, additional income, and strengthening sustainable food security in the peri-urban area of Deket District.